THE EFFECT OF NEWS VIDEO ON STUDENTS’ SPEAKING SKILL AT CLASS X IPA 2 OF SMA NEGEERI 1 LAWE BULAN IN THE ACADEMIC YEAR 2022/2023 - Mardiatul Jannah; Wikiaprian Pinim; Raja Fauziah (Tuwah Pande: Jurnal Ilmu Pendidikan dan Pengajaran, 2024)
A Thesis English Education Department the Faculty of Teachers Training and Education, stkip us Kutacane.The aim of the research was to find out the effect of news video on students’ speaking skill. Language is crucial for communication, and English is an international language. Researcher aim to improve basic English skills by addressing issues in schools like inadequate speaking practice, unmotivated students, and ineffective media. This research uses quantitative techniques for methodical and factual data collection.Ma'ruf Abdullah (2015:124) quantitative research is research that uses quantitative data, namely data in the form of numeric or numbers. The research found that class X IPA 2 students at SMA Negeri 1 Lawe Bulan, their speaking skills were not improved before using video as a medium. So, the researcher applied video as a media in students’ speaking skill. The result research, researcher found the average pre-test score to 56.17, and post-test scores improved to 82.78.Pre-test and post-test data showed a 21.33% difference, indicating a high hypothesis, with a df value of 2,074. There is any improvements by using video as a media in students speaking skill at SMA Negeri 1 Lawe Bulan especially X IPA 2.The researcher may conclude that the results of the study show that the application of video in the student’s speaking ability has an influence in improving the student's speech abilities. it has been proven from the research data results thus the hypothesis is accepted..